Knowledge and attitude towards breastfeeding among fathers working at higher learning institutions in the east coast of Malaysia - Mohd Arifin, Siti Roshaidai; Md. Zaki, Nur Farhana; Daud, Normadiah; Abd. Aziz, Karimah Hanim (Universiti Sultan Zainal Abidin (uniSZA), 2022)
Breastfeeding has many benefits for both mother and baby. Breast milk provides the baby with complete nutrition that supplies energy and reduces illness. Such matters have been well documented with a wide range of studies on breastfeeding among mothers across countries. However, a limited number of studies had been conducted among fathers. It could not be denied that a father plays a significant role in influencing a woman's choice to breastfeed. Lack of husband's support is one of the main barriers to breastfeeding. This study aimed to assess the association between the level of knowledge and attitude on breastfeeding among fathers. A total of 144 fathers working in three higher learning institutions in the east coast region of Malaysia participated in this cross-sectional study. The knowledge and attitude were measured using the Knowledge and Attitude on Breastfeeding Questionnaire. Of these fathers, 57.6% had good knowledge, and 70.8% had a good attitude. Fathers of advanced age were at risk of having poor knowledge. Considering that advanced age could result in poor knowledge, fathers should be educated about breastfeeding. The element of education should be included in an antenatal class.